Influence of ethylene diamine functionalized waste plastic derived reduced graphene oxide as filler on the mechanical and thermal properties of low-density polyethylene - Arya, Tanuja; Rawat, Kundan Singh; Bohra, Bhashkar Singh; Garwal, Kamal; Negi, Pushpa Bhakuni; Tewari, Chetna; Jung, Yong Chae; Sahoo, Nanda Gopal (John Wiley & Sons Inc., 2024)
Reduced graphene oxide (rGO) was prepared from waste plastic using the two steps pyrolysis method and subsequently functionalized with ethylene diamine (EDA) to develop amino-functionalized rGO (EDA-rGO). To make the thermal and mechanical properties more proficient, EDA-rGO was further incorporated as a nanofiller into a low-density polyethylene (LDPE) matrix using the melt mixing method followed by hot-pressing. A variety of analytical methods, such as FT-IR, XRD, XPS, DSC, TGA, DMA, Raman spectroscopy, and HRTEM, were used to characterize the elements and morphology of rGO and EDA-rGO. The results showed that the addition of 5 wt% EDA-rGO to LDPE polymers significantly improved the mechanical and thermal properties, such as storage modulus by 62%, loss modulus by 67%, young's modulus by 123%, tensile strength by 79.83%, respectively. The thermal decomposition temperatures of 5%, 10% and 50% were increased by 14.01, 9.34, and 4.8 degrees C, respectively. This study provides a feasible and ecologically sustainable way of repurposing plastic waste concurrently enhancing the properties of polymer composites.Highlights Synthesis & functionalization of rGO from waste plastic using EDA. EDA-rGO used as a nanofiller to fabricate LDPE polymer nanocomposites. EDA-rGO enhanced the thermal stability of LDPE nanocomposites. The tensile strength & modulus of the LDPE composites are greatly improved. The storage, loss modulus, Tm and Tc enhanced by 62%, 67%, 4.4 degrees C & 2.6 degrees C. Enhanced thermal and mechanical properties of low density polyethylene using waste plastic derived rGO. image